Evaluation of the viability and functionality of human peripheral blood mononuclear cells cryopreserved up to 2 years in animal-protein-free freezing media compared to the FBS-supplemented reference medium - Jantet-Blaudez, Frédérique; Ruiz, Joseline; Gautheron, Sylviane; Pagnon, Anke (Frontiers in Immunology, 2025)
BackgroundCryopreservation of peripheral blood mononuclear cells (PBMCs) is crucial for consistent analysis in immunological studies and clinical trials. Traditional freezing media often contain fetal bovine serum (FBS), which raises ethical concerns and the risk of pathogen transmission, and dimethyl sulfoxide (DMSO), known for its cytotoxic effects. This study evaluates the viability, yield, phenotype, and functionality of PBMCs cryopreserved in several commercially available animal-protein-free media, some with reduced or no DMSO, compared with a reference medium over 2-years.MethodsPBMCs from 11 healthy volunteers were cryopreserved in a reference medium (FBS + 10% DMSO) and nine alternative serum-free media with varying DMSO concentrations. Cell viability and functionality were assessed at 3 weeks (M0), 3 months (M3), 6 months (M6), 1 year (M12), and 2 years (M24) post-freezing. Media with DMSO concentrations below 7.5% were excluded after M0 due to lower viability. Cell functionality was assessed using various assays including cytokine secretion profiles, T and B FluoroSpot, and intracellular cytokine staining.ResultsPBMCs cryopreserved in CryoStor CS10 and NutriFreez D10 maintained high viability and functionality, comparable to the FBS10 reference medium, across all time points. Bambanker D10 displayed a comparable viability but tended to diverge from the FBS10 reference medium in terms of T cell functionality. CryoStor CS7.5, while showing promising results, was eliminated due to being a mixture of CS10 and CS5, which could potentially introduce errors in preparation. Media with < 7.5% DMSO showed significant viability loss and were eliminated after the initial assessments. Serum-free media with 10% DMSO, comparable to FBS-based media, effectively preserved PBMC immune response.ConclusionsCS10 and NutriFreez D10, both serum-free media containing 10% DMSO, are viable alternatives to FBS-based media for the long-term cryopreservation of PBMCs. These media ensure comparable cell viability and functionality, supporting their application in clinical and research settings to address the important drawbacks associated with FBS use.